Proceeding Book 2 Simposium dan Workshop: Continuing profesional development on clinical pathology and laboratory medicine (CPM_CPLM) JogloSemar VIII - Purwanto AP (Joglo Semar Patologi Klinik, 2016)
Proceeding Book 2 Simposium dan Workshop: Continuing profesional development on clinical pathology and laboratory medicine (CPM_CPLM) JogloSemar VIII